Estudio de prescripción- indicación en pacientes que reciben anticonvulsivantes en Colombia - Calvo Torres, Luis Felipe; García Betancur, Santiago; Aguirre Novoa, Alejandra; Bañol Giraldo, Alejandra María; Machado Alba, Jorge Enrique (Revista Médica de Risaralda, 2015)
Estudio